Election [videorecording (DVD)] - Payne, Alexander, 1961-; Taylor, Jim, 1962-; Witherspoon, Reese, 1976-; Broderick, Matthew, 1962-; Klein, Chris, 1979- (Criterion collection, 2017)
Perky, overachieving Tracy Flick gets on the nerves of history teacher Jim McAllister to begin with, but after she launches her campaign for high-school president and his personal life starts to fall apart, things spiral out of control.